Estudo da adsorção de Ácido Lático por cromatografia de troca iônica - Arcanjo, Maria Rosiene Antunes (2014)
Currently the demand for renewable fuels has increased a lot. Thus, biodiesel is an alternative to oil and its derivatives, since its production is cheaper, there is a reduction in emissions, and is considered a renewable energy. Due to government incentives that drive the production of biodiesel, such fuel has been produced on a large scale. Of all the raw material used for producing biodiesel via transesterification, 10 % in mass is converted into glycerin, excess demand and absorption capacity of the current markets. In this context, it is of fundamental importance to develop alternative technologies and innovative at the same time to consume this surplus of crude glycerin. The production of lactic acid by hydrothermal conversion of glycerol is an alternative that adds significantly to the productivity of the biodiesel industry value, besides the production of an organic acid that is widely used industrially. This organic acid exists as two optical isomers, D - lactic acid and L- lactic acid. Presently, it has become an important monomer in the plastics industry, and polymerized biodegradable plastics such as poly-L- lactic acid and copolymers of lactic acid. Therefore, there is a continued interest in a more efficient process for the production of lactic acid as well as for their recovery and purification. Thus, the aim of this study was to conduct a study on the adsorption of lactic acid (derived from the conversion of glycerol resulting from biodiesel production) by ion exchange by Amberlite IRA 67 and IRA 96. Different eluents were evaluated at various concentrations in order to obtain a higher efficiency in removing lactic acid adsorbents studied. From the breakthrough curves obtained with different concentrations of lactic power (60-302 g/L) acid the adsorption isotherms were constructed at temperatures of 30 °C, 40 °C and 60 °C. With data from lactic acid concentration for each condition studied, became the model fit the Langmuir adsorption isotherm. Studies on the purification column fixed bed with mono-component solutions, binary mixtures and real mixture were also performed. It was concluded that the application of the proposed methodology for the purification of lactic acid in a fixed-bed column showed better results when the condition (temperature = 30 °C) was used in both adsorbents. As the Amberlite IRA 96, the adsorbent showed better performance in the adsorption of lactic acid.